Kriminalisasi Kohabitasi Dalam Pasal 412 Undang-undang Nomor 1 Tahun 2023 tentang Kitab Undang-undang Hukum Pidana Sebagai Upaya Perlindungan Hak Asasi Manusia Pelaku Dari Tindakan Main Hakim Sendiri (Eigenrechting) - Frinza Akitha; Patricia Rinwigati (Pusat Riset dan Inovasi Nasional, 2025)
Indonesia has updated its Criminal Code through Law Number 1 of 2023, making a legal breakthrough by criminalizing cohabitation. Prior to this legislation, cohabitation was legally permitted but often considered contrary to social norms. In several Indonesian regions, cohabitants caught by local communities have been subjected to vigilante justice. Conversely, cohabitation can be viewed through the lens of human rights, where individuals possess the fundamental right to choose their life partners within or outside marriage. Consequently, the state is obligated to respect and protect this right from potential interference by other societal actors. This research examines whether the criminalization of cohabitation constitutes a human rights violation. Utilizing a doctrinal research methodology with a statutory approach, the study argues that the criminalization represents a nuanced compromise reflecting the current social and legal landscape in Indonesia.